Hydrogen and valuable liquid fuel production from the in-situ pyrolysis-catalytic steam reforming reactions of cellulose bio-polymer wastes dissolved in phenol over trimetallic Ni-La-Pd/TiCa nanocatalysts. Issue 2 (April 2023) - Nabgan, Walid; Tuan Abdullah, T.A.; Ikram, M.; Owgi, A.H.K.; Hatta, A.H.; Alhassan, M.; Aziz, F.F.A.; Jalil, A.A.; Van Tran, Thuan; Djellabi, Ridha
Abstract: Hydrogen and liquid fuel production from biopolymer waste, such as cellulose dissolved in phenol, was investigated using in-situ pyrolysis-catalytic steam reforming conditions. Developing a sustainable method for the thermal cracking of such biopolymers still faces difficulties due to the catalyst stability primarily impacted by coke deposition. The key to the proposed method is improving a highly active and stable catalytic reforming process in which trimetallic Ni-La-Pd supported on TiCa acts as a primary reforming catalyst. Catalysts were prepared by hydrothermal, and impregnation techniques, and the physicochemical characteristics of the fresh and spent materials were examined. The results showed that the NLP/TiCa catalysts performed effectively due to their comparatively high surface area, strong basicity, evenly distributed Pd particles, and appropriate redox and desorption characteristics. The addition of Pd retards the reducibility of the NL/TiCa; therefore, a Pd*La, La*Ni, La*Ti, and Ca*Ti interaction exist. Almost complete conversion of phenol (98.7%) and maximum H2 yield (99.6%) were achieved at 800 °C for the NLP/TiCa. These findings give an insight into industrial-scale development. They have significant potential for enhancing the generation of hydrogen and liquid products from phenol and cellulose waste, such as propanol, ethanol, toluene, etc. Graphical Abstract: ga1 Highlights: Trimetallic Ni-La-Pd supported on Ti-Ca nano-catalysts were synthesized. Hydrogen and liquid production from cellulose dissolved in phenol was studied. NLP/TiCa catalyst was highly active due to its basicity and reducibility features. The liquid products mainly contained propanol, ethanol, and toluene.